Advanced Endoscopy - Yan, Qiang; Sun, Xu; Yan, Qiang; Sun, Xu (IntechOpen, 2020)
With the rapid development of modern medical technology, endoscopic technology has also achieved unprecedented development. Its fields cover examination, treatment, surgery, and even molecular imaging diagnosis. Endoscopy technology brings a minimally invasive diagnosis and treatment experience to patients. Invasive treatment and examination of digestive surgery has changed from large incisions to several Trocar holes, from surgery to endoscopic treatment, and from laparotomy to endoscopy or laparoscopy, which has changed the diagnosis treatment and management of digestive surgery, enhanced the recovery after surgery, and benefited the patients needing to undergo surgical procedures. It is for this reason that we plan to introduce the development of endoscopic and laparoscopic surgery in digestive surgery and enhanced rehabilitation medicine.
English
Keywords: Psychotherapy; Medical imaging